Review of small ruminant research and development activities in Ethiopia - Awgichew, K.; Hailu, G. (1986)
Discusses the economic importance of small ruminants in the national livestock economies in Ethiopia. Looks at major constraints like feeding and marketing and discusses social factors that hindered the development of sheep and goat industry. The current and future research and development priorities set by a technical committee were reviewed.